Some Plant Defense Stimulators can induce IL-1β production in human immune cells in vitro - Lény Teyssier; Gabriele Sorci; Johanna Chluba; Sébastien Aimé; David Wendehenne; Olivier Lamotte; Jean-Louis Connat (Toxicology Reports, 2020)
Among Plant Protection Products (PPP), a new emerging category of pesticides act by stimulating plant defense in order to improve plant resistance against microbial pathogens. Given that these compounds, the so-called Plant Defense Stimulators (PDS) act on innate immunity, we tested, using an in vitro approach on human mononuclear leucocytes (PBMC), the potential toxicity (XTT assay) and inflammatory effects (production of IL-1β) of 4 PPP belonging to different chemical families. We found that two products (LBG-01F34® and Regalis®) did not induce any cytotoxicity or IL-1 β production. The product BION-50 WG®, that contains Acibenzolar-S-methyl (ASM) and silica particles did not present any cytotoxicity but induced a significant increase in the production of the inflammatory cytokine IL-1 β. Finally, Vacciplant® that contains laminarin, was highly cytotoxic and pro-inflammatory. It induced a strong production of IL-1 β when used at a concentration in the culture medium, as low as 0.02 mg/mL. We also tested the potential toxic effect of these 4 PPP on 4 days old zebra fish larvae. After 24 h of exposure, our results indicate that Vacciplant® induced zebra fish larvae mortality at concentration of 20 μg/mL. LBG did not induced significant mortality at concentrations up to 1 mg/mL whereas Regalis was lethal for 0,3 mg/mL concentrations and BION-50 WG began to induce mortality at 2,5 mg/mL.Our results indicate possible effects of PDS on IL-1β production in human cells and fish survival, calling for more studies on the potential noxious side effects of these compounds.